Associations between polymorphisms in the IL-4 gene and renal cell carcinoma in Chinese Han population - Rong, Hao (Oncotarget, 2017)
Renal cell carcinoma (RCC) is considered to be a kind of cytokine reactive tumor. The research has been suggested that the host immune system can regulate the clinical course of RCC. Therefore, cytokine gene polymorphisms in RCC patients were analyzed was necessary. Our study is purpose to analyzing the interleukin-4(IL-4) polymorphisms associated with RCC risk from Han Chinese population. IL-4 genetic polymorphisms were genotyped using Massarray technology from a total of 291RCC and 463 controls. Unconditional logistic regression analysis was performed to analyze their relationship with risk of RCC. A significant association was found between the rs2243250 “C” allel and decreased risk of RCC (OR=0.75, 95%CI=0.59-0.96, P=0.02). Stratified analysis based on the age, gender, smoking status, drinking status revealed no significant association with RCC in age>55, female, smoking and nodrinking. However, for age<55 group (rs2243250, rs2243267, rs2243270), male group (rs2243250), nonsmoking group (rs2227284), and drinking group (rs2243250, rs2227284, rs2243267, rs2243270) polymorphisms were found obviously associated with RCC. The haplotype analyses showed that the haplotype have a significant decreased risk of RCC in the rs2243250/rs2227284/rs2243267/rs2243270/rs2243283/rs2243289 (CGGACA) (Total, OR=0.73, 95%CI=0.54-0.98, P=0.034; Male, OR=0.59, 95%CI=0.39-0.90, P=0.014). Therefore, the present study suggests that IL-4 may be a candidate gene for assessing the risk of RCC.